Nuclear energy-economic growth nexus in OECD countries: A panel data analysis - Ozcan, Burcu; Ari, Ayse (International Economic Society, 2017)
In this study, our purpose was to analyze the relationship between nuclear energy consumption and economic growth in 13 OECD countries from 1980 to 2012, based on the framework of panel cointegration and causality analyses. The panel causality results supported the feedback hypothesis in both the short-run and long-run. In other words, there is a positive relationship between nuclear energy consumption and economic growth. As such, nuclear energy consumption and economic growth complement and reinforce each other, and thus nuclear energy conservation policies may negatively affect the economic growth rates of OECD countries under study. Besides, the long-run estimation results indicated that nuclear energy consumption has a positive and significant impact on real GDP in 6 out of 13 countries, namely Germany, Netherlands, Sweden, UK, Switzerland, and South Korea. Also, for the whole OECD panel set, the long-run results indicated that labor force, physical capital and nuclear energy consumption have positive and significant impacts on the economic growth. Based on the findings, important policy implications were also provided. © International Economic Society.
Keywords: Economic growth; Nuclear energy; Panel causality test; Panel cointegration test